An Introduction to Multi Inner Product Space - Das, Sujoy (Communications in Mathematics and Applications, 2022)
In this paper, for the first time, notion of multi complex numbers and multi complex number valued inner product is introduced in multi linear (vector) space. Starting from the definition, some basic properties of multi inner product spaces are studied along with examples. Multi number valued parallelogram law and polarization identity are established in multi inner product space.